Effect of Employee Discipline and Employment Conflict on Employee Achievement of PT. Dodorindo Jaya Abadi Tanjung morawa - Erika Erika; Robin Robin (Institute of Computer Science (IOCS), 2022)
This study aims to determine whether there is an influence of discipline and work conflict on the work performance of employees. The population in this study were all employees who worked at PT. Dodorindo Jaya Abadi Tanjung Morawa as many as 447 employees. The sampling technique used was the Slovin technique with a significance of 10% with a sample of 82 employees. In this study, a questionnaire will be distributed which is measured by a Likert scale. Data analysis used multiple linear regression analysis. The results showed that there was an effect both partially and simultaneously where the discipline variable partially had a tcount (6.844) greater than ttable (1.990) with a significant (0.00) less than 0.05, while the work conflict variable had a tcount value. . (-3.269) is smaller than ttable (-1.990) with a significant (0.00) smaller than 0.05. Simultaneously, the variables of discipline and work conflict have a value of Ftable (3.11) and a significance = 5% (0.05), namely Fcount (31.039) and sig.a (0.000a). This shows that the results of the study accept Ha and reject H0, while the coefficient of determination R Square is 0.426. This shows that the variables of discipline and work conflict explain their influence on the work performance by 42.6%. While the remaining 57.4% is the influence of other independent variables.